2015
DOI: 10.1186/s13075-015-0664-8
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptor 2 (TLR2) induces migration and invasive mechanisms in rheumatoid arthritis

Abstract: IntroductionThis study investigates the role of Toll-like receptor 2 (TLR2) in the regulation of migratory and invasive mechanisms in rheumatoid arthritis (RA).MethodsInvasion, migration, matrix metalloproteinase (MMP)-1, -3 and tissue inhibitor of matrix metalloproteinase-3 (TIMP-3) expression, β-integrin binding, cytoskeletal rearrangement and Ras-related C3 botulinum toxin substrate 1 (Rac1) activation in response to a TLR2-ligand, Pam3CSK4 (1 μg/ml), in ex vivo RA synovial tissue explants, primary RA synov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 63 publications
3
45
0
2
Order By: Relevance
“…In addition, we report that TLR2 engagement induces a cytoskeletal rearrangement by augmenting the degree of actin polymerization. Our findings are in agreement with a previous work, which has revealed that Pam3CSK4 alters cytoskeletal dynamics (68). However, it should be noted that this work was carried out in human fibroblasts and not in CD4 ϩ T cells, as shown here.…”
Section: Figsupporting
confidence: 81%
See 1 more Smart Citation
“…In addition, we report that TLR2 engagement induces a cytoskeletal rearrangement by augmenting the degree of actin polymerization. Our findings are in agreement with a previous work, which has revealed that Pam3CSK4 alters cytoskeletal dynamics (68). However, it should be noted that this work was carried out in human fibroblasts and not in CD4 ϩ T cells, as shown here.…”
Section: Figsupporting
confidence: 81%
“…Although TLR2 triggering does not affect surface expression levels of CCR5 and CD4, we quantified the extent of virus entry because it has been shown recently that Pam3CSK4 induces rearrangement of the F-actin cytoskeletal architecture (68). We performed an entry test using NL4.3 Balenv viruses and quantified the intracellular p24 content by enzymelinked immunosorbent assay (ELISA) in CD3/CD28-costimulated CD4 ϩ T cells that were either left untreated or treated with Pam3CSK4.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, TLR2 is expressed in SM perivascular regions,50 and in vitro TLR2 activation induces VEGF/IL-8 expression in synovial fibroblasts and chondrocytes,51 52 and MMP-9 in corneal epithelial cells and THP-1 macrophages 53. Furthermore, we have demonstrated using whole-tissue RA synovial explant cultures that OPN301 significantly inhibits spontaneous release of pro-inflammatory cytokines IL-1β, TNF-α, IFN-γ and IL-8, 34 and MMP-3, MMP-2 and MMP-9 54. In addition, culture of RASFC with conditioned media from OPN301-treated RA explants inhibited RASFC migration and invasion compared with IgG control 54.…”
Section: Discussionmentioning
confidence: 78%
“…Furthermore, we have demonstrated using whole-tissue RA synovial explant cultures that OPN301 significantly inhibits spontaneous release of pro-inflammatory cytokines IL-1β, TNF-α, IFN-γ and IL-8, 34 and MMP-3, MMP-2 and MMP-9 54. In addition, culture of RASFC with conditioned media from OPN301-treated RA explants inhibited RASFC migration and invasion compared with IgG control 54. Therefore, the ability of TLR2 to mediate A-SAA-induced changes in vascularity, chemokine expression and adhesion further support the hypothesis that A-SAA engages TLR2 to act locally in the RA joint.…”
Section: Discussionmentioning
confidence: 98%
“…Активация ТПР2 в синовиальных фибробластах у больных РА приводила к увеличению продукции большого количе-ства провоспалительных цитокинов, включая ИЛ1β и ФНОα [20,21]. В исследованиях на культурах клеток бы-ла показана связь между активацией ТПР2 и повышенным синтезом ММП, обладающих выраженной катаболиче-ской активностью, а также белка RANKL (receptor activator of nuclear factor kappa-B ligand; лиганд рецептора, активи-рующего ядерный фактор каппа-В), активирующего остео-кластогенез [22,23]. Отмечена статистически значимая связь экспрессии ТПР2 и 4 с синтезом ИЛ12 и ИЛ18 в си-новиальной ткани пациентов с РА [19].…”
unclassified